Wild bird trafficking in Brazil and the veterinary physician’s activities - Carinhato, R. A. P.; Sanches, J. M.; Masseno, A. P. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2018)
The Brazilian fauna has a high biodiversity,introducing about 10% of 1,400,000 animals cataloguedon the planet (BRASIL, 2002). This data makes Brazil asa target country in the trade of wild animals. Accordingto Rede Nacional Contra o Tráfico de Animais Silvestres([2012?]) surveys, it was concluded that: About 80% of thesmuggled animals are birds, moving around R$ 3 billion.Therefore, the large amount of money involved in the purchaseof animals combined with the high level of povertyin certain regions of Brazil, is the reason that can promoteseven more the illegal trade. In addition, the capture of wildanimals is linked to the use of members of the fauna as pets,source of income and as food (FREITAS et al., 2015). Animportant point for the conservation of wild birds is theknowledge of the fauna that is kept illegally. It is necessarythe analysis of the species, number of specimens, animalhealth conditions and the appropriate treatment to be performedto return them to the homeostasis. To all of these assumptions the Veterinarian is essential profession. Afterthe rescue of these birds and their appropriated treatment,their main destination is returning them to the nature(RIBEIRO; SILVA, 2007). This paper performs an analysisof birds traffic in Brazil and discuss the importance of theveterinarians in the control of this practice.